Sistem Informasi Persedian Dan Penjualan Busana Muslim - Ulfah Indriani (U-NET Jurnal Teknik Informatika, 2022)
Lysen Surono Central Shop Medan Market is engaged in selling Muslim Clothing. However, sales activities are still carried out manually, marketing and product promotion covers only a very limited area and only relies on marketing systems by telephone ordering and product introduction is still done manually, to see information about the products needed, customers must come to the store to find out detailed information thereby hampering the sales process carried out by Lysen Surono Central Shop Medan Market. Sales at the Lysen Surono Central Medan Market Shop have been slow and inefficient, both in terms of cost and time when the running system is running using the traditional method, as previously described. So we need a system that can help the inventory system and sales and management of Muslim Clothing data. In order to make it easier for staff in making data reports Muslim Clothing. With the web-based Muslim Clothing Supply and Sales Application proposed at the Lysen Surono Central Shop Medan Market is able to produce information that is fast, and timely making it easier in processing Muslim Clothing sales data.